2023
DOI: 10.1037/mot0000283
|View full text |Cite
|
Sign up to set email alerts
|

Flexible control: Conflict mindsets reduce the association between trait measures of self-control decision-making and delay discounting.

Abstract: People experience conflicts between goals, thoughts, and actions on a regular basis. Those conflict experiences can trigger a conflict mindset, a unique information processing style characterized by the activation and consideration of conflicting alternatives. This processing style has been associated with a reduced reliance on dominant or default response tendencies. It could, therefore, affect self-control decisions, in which in order to receive a larger delayed reward (e.g., good health) people need to fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Attitude shift away from exaggerated positions in this direction. Becker et al (2023) showed that after recalling conflicting goals (see Stern & Kleiman, 2015), interindividual differences in impulsivity no longer predicted a preference for immediate over delayed rewards in choice tasks. Hence, goal conflicts reduced behavioral responses in line with traits.…”
Section: Goal Conflictsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attitude shift away from exaggerated positions in this direction. Becker et al (2023) showed that after recalling conflicting goals (see Stern & Kleiman, 2015), interindividual differences in impulsivity no longer predicted a preference for immediate over delayed rewards in choice tasks. Hence, goal conflicts reduced behavioral responses in line with traits.…”
Section: Goal Conflictsmentioning
confidence: 99%
“…Any task or instruction with the potential to prepare individuals for these operations could serve as a cornerstone of an intervention against extreme attitudes. Intraindividual conflicts might also elicit negative affect, but we did not find evidence that is driving the impact of goal conflicts (e.g., Becker et al, 2023). Therefore, we assume that flexibility is the relevant process variable.…”
Section: Summary and Implicationsmentioning
confidence: 99%